Effect of different fertilizers on microbial biomass carbon, respiration and yield under a lettuce crop - Costantini, Alejandro; Segat, Andrea; Almeida, Dejair Lopes de; de-Polli, Helvécio (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this work was to evaluate the effect of two fertilizers on microbial biomass carbon, soil respiration and yield components of lettuce (Lactuca sativa L.). A field trial was carried out on a typic Hapludult soil located at Rio de Janeiro State, Brazil. On a completely randomized block design the effect of two fertilizers, urea and vermicomposting were analyzed, each one at three levels with all the possible combinations. The variables studied were microbial biomass carbon (MBC), soil respiration, qCO2 and dry matter yield. Seven samplings were performed during the crop cycle, from one month before transplanting to a few days after harvest. MBC and respiration values were higher during the first month following the manure incorporation and in plots where the highest levels of fertilizer were applied. These differences are observed during the first samplings, but later, they became practically insignificant. Probably, fertilizer losses were important. No differences were found in relation to the incorporation of vermicomposting. During the first three samplings organic carbon content was assessed. At the time of fertilizers incorporation, the highest values were obtained, but at the following sampling, their values decreased. The highest urea levels, the greatest yield. MBC contents are correlated with the aerial dry matter.